# Theory Coding_Predicates

```chapter ‹Predicates for Terms, Formulas and Substitution›

theory Coding_Predicates
imports Coding Sigma
begin

declare succ_iff [simp del]

text ‹This material comes from Section 3, greatly modified for de Bruijn syntax.›

section ‹Predicates for atomic terms›

subsection ‹Free Variables›

definition VarP :: "tm ⇒ fm" where "VarP x ≡ OrdP x AND Zero IN x"

lemma VarP_eqvt [eqvt]: "(p ∙ VarP x) = VarP (p ∙ x)"

lemma VarP_fresh_iff [simp]: "a ♯ VarP x ⟷ a ♯ x"

lemma VarP_sf [iff]: "Sigma_fm (VarP x)"
by (auto simp: VarP_def)

lemma VarP_subst [simp]: "(VarP x)(i::=t) = VarP (subst i t x) "

lemma VarP_cong: "H ⊢ x EQ x' ⟹ H ⊢ VarP x IFF VarP x'"
by (rule P1_cong) auto

lemma VarP_HPairE [intro!]: "insert (VarP (HPair x y)) H ⊢ A"
by (auto simp: VarP_def)

subsection ‹De Bruijn Indexes›

abbreviation Q_Ind :: "tm ⇒ tm"
where "Q_Ind k ≡ HPair (HTuple 6) k"

nominal_function IndP :: "tm ⇒ fm"
where "atom m ♯ x ⟹
IndP x = Ex m (OrdP (Var m) AND x EQ HPair (HTuple 6) (Var m))"
by (auto simp: eqvt_def IndP_graph_aux_def flip_fresh_fresh) (metis obtain_fresh)

nominal_termination (eqvt)
by lexicographic_order

lemma
shows IndP_fresh_iff [simp]: "a ♯ IndP x ⟷ a ♯ x"                (is ?thesis1)
and IndP_sf [iff]:         "Sigma_fm (IndP x)"                   (is ?thsf)
and OrdP_IndP_Q_Ind:       "{OrdP x} ⊢ IndP (Q_Ind x)"           (is ?thqind)
proof -
obtain m::name where "atom m ♯ x"
by (metis obtain_fresh)
thus ?thesis1 ?thsf ?thqind
by (auto intro: Ex_I [where x=x])
qed

lemma IndP_Q_Ind: "H ⊢ OrdP x ⟹ H ⊢ IndP (Q_Ind x)"
by (rule cut1 [OF OrdP_IndP_Q_Ind])

lemma subst_fm_IndP [simp]: "(IndP t)(i::=x) = IndP (subst i x t)"
proof -
obtain m::name where "atom m ♯ (i,t,x)"
by (metis obtain_fresh)
thus ?thesis
by (auto simp: IndP.simps [of m])
qed

lemma IndP_cong: "H ⊢ x EQ x' ⟹ H ⊢ IndP x IFF IndP x'"
by (rule P1_cong) auto

subsection ‹Various syntactic lemmas›

section ‹The predicate ‹SeqCTermP›, for Terms and Constants›

(*SeqCTerm(s,k,t) ≡ LstSeq(s,k,t) ∧ (∀l∈k)[s l=0 ∨ Var(s l)∨(∃m,n∈l)[s l = ⟨Eats, s m, s n⟩]]*)
nominal_function SeqCTermP :: "bool ⇒ tm ⇒ tm ⇒ tm ⇒ fm"
where "⟦atom l ♯ (s,k,sl,m,n,sm,sn);  atom sl ♯ (s,m,n,sm,sn);
atom m ♯ (s,n,sm,sn);  atom n ♯ (s,sm,sn);
atom sm ♯ (s,sn);  atom sn ♯ (s)⟧ ⟹
SeqCTermP vf s k t =
LstSeqP s k t AND
All2 l (SUCC k) (Ex sl (HPair (Var l) (Var sl) IN s AND
(Var sl EQ Zero OR (if vf then VarP (Var sl) else Fls) OR
Ex m (Ex n (Ex sm (Ex sn (Var m IN Var l AND Var n IN Var l AND
HPair (Var m) (Var sm) IN s AND HPair (Var n) (Var sn) IN s AND
Var sl EQ Q_Eats (Var sm) (Var sn))))))))"
by (auto simp: eqvt_def SeqCTermP_graph_aux_def flip_fresh_fresh) (metis obtain_fresh)

nominal_termination (eqvt)
by lexicographic_order

lemma
shows SeqCTermP_fresh_iff [simp]:
"a ♯ SeqCTermP vf s k t ⟷ a ♯ s ∧ a ♯ k ∧ a ♯ t"  (is ?thesis1)
and SeqCTermP_sf [iff]:
"Sigma_fm (SeqCTermP vf s k t)"   (is ?thsf)
and SeqCTermP_imp_LstSeqP:
"{ SeqCTermP vf s k t } ⊢ LstSeqP s k t"  (is ?thlstseq)
and SeqCTermP_imp_OrdP [simp]:
"{ SeqCTermP vf s k t } ⊢ OrdP k"  (is ?thord)
proof -
obtain l::name and sl::name and m::name and n::name and sm::name and sn::name
where atoms: "atom l ♯ (s,k,sl,m,n,sm,sn)"   "atom sl ♯ (s,m,n,sm,sn)"
"atom m ♯ (s,n,sm,sn)"   "atom n ♯ (s,sm,sn)"
"atom sm ♯ (s,sn)"   "atom sn ♯ (s)"
by (metis obtain_fresh)
thus ?thesis1 ?thsf ?thlstseq ?thord
by (auto simp: LstSeqP.simps)
qed

lemma SeqCTermP_subst [simp]:
"(SeqCTermP vf s k t)(j::=w) = SeqCTermP vf (subst j w s) (subst j w k) (subst j w t)"
proof -
obtain l::name and sl::name and m::name and n::name and sm::name and sn::name
where "atom l ♯ (j,w,s,k,sl,m,n,sm,sn)"   "atom sl ♯ (j,w,s,m,n,sm,sn)"
"atom m ♯ (j,w,s,n,sm,sn)"   "atom n ♯ (j,w,s,sm,sn)"
"atom sm ♯ (j,w,s,sn)"   "atom sn ♯ (j,w,s)"
by (metis obtain_fresh)
thus ?thesis
by (force simp add: SeqCTermP.simps [of l _ _ sl m n sm sn])
qed

declare SeqCTermP.simps [simp del]

abbreviation SeqTermP :: "tm ⇒ tm ⇒ tm ⇒ fm"
where "SeqTermP ≡ SeqCTermP True"

abbreviation SeqConstP :: "tm ⇒ tm ⇒ tm ⇒ fm"
where "SeqConstP ≡ SeqCTermP False"

lemma SeqConstP_imp_SeqTermP: "{SeqConstP s k t} ⊢ SeqTermP s k t"
proof -
obtain l::name and sl::name and m::name and n::name and sm::name and sn::name
where "atom l ♯ (s,k,t,sl,m,n,sm,sn)"   "atom sl ♯ (s,k,t,m,n,sm,sn)"
"atom m ♯ (s,k,t,n,sm,sn)"   "atom n ♯ (s,k,t,sm,sn)"
"atom sm ♯ (s,k,t,sn)"   "atom sn ♯ (s,k,t)"
by (metis obtain_fresh)
thus ?thesis
apply (auto simp: SeqCTermP.simps [of l s k sl m n sm sn])
apply (rule Ex_I [where x="Var l"], auto)
apply (rule Ex_I [where x = "Var sl"], force intro: Disj_I1)
apply (rule Ex_I [where x = "Var sl"], simp)
apply (rule Conj_I, blast)
apply (rule Disj_I2)+
apply (rule Ex_I [where x = "Var m"], simp)
apply (rule Ex_I [where x = "Var n"], simp)
apply (rule Ex_I [where x = "Var sm"], simp)
apply (rule Ex_I [where x = "Var sn"], auto)
done
qed

section ‹The predicates ‹TermP› and ‹ConstP››

subsection ‹Definition›

nominal_function CTermP :: "bool ⇒ tm ⇒ fm"
where "⟦atom k ♯ (s,t); atom s ♯ t⟧ ⟹
CTermP vf t = Ex s (Ex k (SeqCTermP vf (Var s) (Var k) t))"
by (auto simp: eqvt_def CTermP_graph_aux_def flip_fresh_fresh) (metis obtain_fresh)

nominal_termination (eqvt)
by lexicographic_order

lemma
shows CTermP_fresh_iff [simp]: "a ♯ CTermP vf t ⟷ a ♯ t"            (is ?thesis1)
and CTermP_sf [iff]: "Sigma_fm (CTermP vf t)"                      (is ?thsf)
proof -
obtain k::name and s::name  where "atom k ♯ (s,t)" "atom s ♯ t"
by (metis obtain_fresh)
thus ?thesis1 ?thsf
by auto
qed

lemma CTermP_subst [simp]: "(CTermP vf i)(j::=w) = CTermP vf (subst j w i)"
proof -
obtain k::name and s::name  where "atom k ♯ (s,i,j,w)" "atom s ♯ (i,j,w)"
by (metis obtain_fresh)
thus ?thesis
by (simp add: CTermP.simps [of k s])
qed

abbreviation TermP :: "tm ⇒ fm"
where "TermP ≡ CTermP True"

abbreviation ConstP :: "tm ⇒ fm"
where "ConstP ≡ CTermP False"

subsection ‹Correctness properties for constants›

lemma ConstP_imp_TermP: "{ConstP t} ⊢ TermP t"
proof -
obtain k::name and s::name  where "atom k ♯ (s,t)" "atom s ♯ t"
by (metis obtain_fresh)
thus ?thesis
apply auto
apply (rule Ex_I [where x = "Var s"], simp)
apply (rule Ex_I [where x = "Var k"], auto intro: SeqConstP_imp_SeqTermP [THEN cut1])
done
qed

section ‹Abstraction over terms›

nominal_function SeqStTermP :: "tm ⇒ tm ⇒ tm ⇒ tm ⇒ tm ⇒ tm ⇒ fm"
where "⟦atom l ♯ (s,k,v,i,sl,sl',m,n,sm,sm',sn,sn');
atom sl ♯ (s,v,i,sl',m,n,sm,sm',sn,sn'); atom sl' ♯ (s,v,i,m,n,sm,sm',sn,sn');
atom m ♯ (s,n,sm,sm',sn,sn'); atom n ♯ (s,sm,sm',sn,sn');
atom sm ♯ (s,sm',sn,sn'); atom sm' ♯ (s,sn,sn');
atom sn ♯ (s,sn'); atom sn' ♯ s⟧ ⟹
SeqStTermP v i t u s k =
VarP v AND LstSeqP s k (HPair t u) AND
All2 l (SUCC k) (Ex sl (Ex sl' (HPair (Var l) (HPair (Var sl) (Var sl')) IN s AND
(((Var sl EQ v AND Var sl' EQ i) OR
((IndP (Var sl) OR Var sl NEQ v) AND Var sl' EQ Var sl)) OR
Ex m (Ex n (Ex sm (Ex sm' (Ex sn (Ex sn' (Var m IN Var l AND Var n IN Var l AND
HPair (Var m) (HPair (Var sm) (Var sm')) IN s AND
HPair (Var n) (HPair (Var sn) (Var sn')) IN s AND
Var sl EQ Q_Eats (Var sm) (Var sn) AND
Var sl' EQ Q_Eats (Var sm') (Var sn')))))))))))"
apply (simp_all add: eqvt_def SeqStTermP_graph_aux_def flip_fresh_fresh)
by auto (metis obtain_fresh)

nominal_termination (eqvt)
by lexicographic_order

lemma
shows SeqStTermP_fresh_iff [simp]:
"a ♯ SeqStTermP v i t u s k ⟷ a ♯ v ∧ a ♯ i ∧ a ♯ t ∧ a ♯ u ∧ a ♯ s ∧ a ♯ k"  (is ?thesis1)
and SeqStTermP_sf [iff]:
"Sigma_fm (SeqStTermP v i t u s k)"  (is ?thsf)
and SeqStTermP_imp_OrdP:
"{ SeqStTermP v i t u s k } ⊢ OrdP k"  (is ?thord)
and SeqStTermP_imp_VarP:
"{ SeqStTermP v i t u s k } ⊢ VarP v"  (is ?thvar)
and SeqStTermP_imp_LstSeqP:
"{ SeqStTermP v i t u s k } ⊢ LstSeqP s k (HPair t u)"  (is ?thlstseq)
proof -
obtain l::name and sl::name and sl'::name and m::name and n::name and
sm::name and sm'::name and sn::name and sn'::name
where atoms:
"atom l ♯ (s,k,v,i,sl,sl',m,n,sm,sm',sn,sn')"
"atom sl ♯ (s,v,i,sl',m,n,sm,sm',sn,sn')" "atom sl' ♯ (s,v,i,m,n,sm,sm',sn,sn')"
"atom m ♯ (s,n,sm,sm',sn,sn')" "atom n ♯ (s,sm,sm',sn,sn')"
"atom sm ♯ (s,sm',sn,sn')" "atom sm' ♯ (s,sn,sn')"
"atom sn ♯ (s,sn')" "atom sn' ♯ (s)"
by (metis obtain_fresh)
thus ?thesis1 ?thsf ?thord ?thvar ?thlstseq
by (auto intro: LstSeqP_OrdP)
qed

lemma SeqStTermP_subst [simp]:
"(SeqStTermP v i t u s k)(j::=w) =
SeqStTermP (subst j w v) (subst j w i) (subst j w t) (subst j w u) (subst j w s) (subst j w k)"
proof -
obtain l::name and sl::name and sl'::name and m::name and n::name and
sm::name and sm'::name and sn::name and sn'::name
where "atom l ♯ (s,k,v,i,w,j,sl,sl',m,n,sm,sm',sn,sn')"
"atom sl ♯ (s,v,i,w,j,sl',m,n,sm,sm',sn,sn')"
"atom sl' ♯ (s,v,i,w,j,m,n,sm,sm',sn,sn')"
"atom m ♯ (s,w,j,n,sm,sm',sn,sn')" "atom n ♯ (s,w,j,sm,sm',sn,sn')"
"atom sm ♯ (s,w,j,sm',sn,sn')" "atom sm' ♯ (s,w,j,sn,sn')"
"atom sn ♯ (s,w,j,sn')" "atom sn' ♯ (s,w,j)"
by (metis obtain_fresh)
thus ?thesis
by (force simp add: SeqStTermP.simps [of l _ _ _ _ sl sl' m n sm sm' sn sn'])
qed

lemma SeqStTermP_cong:
"⟦H ⊢ t EQ t'; H ⊢ u EQ u'; H ⊢ s EQ s'; H ⊢ k EQ k'⟧
⟹ H ⊢ SeqStTermP v i t u s k IFF SeqStTermP v i t' u' s' k'"
by (rule P4_cong [where tms="[v,i]"]) (auto simp: fresh_Cons)

declare SeqStTermP.simps [simp del]

subsection ‹Defining the syntax: main predicate›

nominal_function AbstTermP :: "tm ⇒ tm ⇒ tm ⇒ tm ⇒ fm"
where "⟦atom s ♯ (v,i,t,u,k); atom k ♯ (v,i,t,u)⟧ ⟹
AbstTermP v i t u =
OrdP i AND Ex s (Ex k (SeqStTermP v (Q_Ind i) t u (Var s) (Var k)))"
by (auto simp: eqvt_def AbstTermP_graph_aux_def flip_fresh_fresh) (metis obtain_fresh)

nominal_termination (eqvt)
by lexicographic_order

lemma
shows AbstTermP_fresh_iff [simp]:
"a ♯ AbstTermP v i t u ⟷ a ♯ v ∧ a ♯ i ∧ a ♯ t ∧ a ♯ u"  (is ?thesis1)
and AbstTermP_sf [iff]:
"Sigma_fm (AbstTermP v i t u)"  (is ?thsf)
and AbstTermP_imp_VarP:
"{ AbstTermP v i t u } ⊢ VarP v"   (is ?thvar)
and AbstTermP_imp_OrdP:
"{ AbstTermP v i t u } ⊢ OrdP i"   (is ?thord)
proof -
obtain s::name and k::name where "atom s ♯ (v,i,t,u,k)"  "atom k ♯ (v,i,t,u)"
by (metis obtain_fresh)
thus ?thesis1 ?thsf ?thvar ?thord
by (auto intro: SeqStTermP_imp_VarP thin2)
qed

lemma AbstTermP_subst [simp]:
"(AbstTermP v i t u)(j::=w) = AbstTermP (subst j w v) (subst j w i) (subst j w t) (subst j w u)"
proof -
obtain s::name and k::name  where "atom s ♯ (v,i,t,u,w,j,k)"  "atom k ♯ (v,i,t,u,w,j)"
by (metis obtain_fresh)
thus ?thesis
by (simp add: AbstTermP.simps [of s _ _ _ _ k])
qed

declare AbstTermP.simps [simp del]

section ‹Substitution over terms›

subsection ‹Defining the syntax›

nominal_function SubstTermP :: "tm ⇒ tm ⇒ tm ⇒ tm ⇒ fm"
where "⟦atom s ♯ (v,i,t,u,k); atom k ♯ (v,i,t,u)⟧ ⟹
SubstTermP v i t u = TermP i AND Ex s (Ex k (SeqStTermP v i t u (Var s) (Var k)))"
by (auto simp: eqvt_def SubstTermP_graph_aux_def flip_fresh_fresh) (metis obtain_fresh)

nominal_termination (eqvt)
by lexicographic_order

lemma
shows SubstTermP_fresh_iff [simp]:
"a ♯ SubstTermP v i t u ⟷ a ♯ v ∧ a ♯ i ∧ a ♯ t ∧ a ♯ u"  (is ?thesis1)
and SubstTermP_sf [iff]:
"Sigma_fm (SubstTermP v i t u)"     (is ?thsf)
and SubstTermP_imp_TermP:
"{ SubstTermP v i t u } ⊢ TermP i"  (is ?thterm)
and SubstTermP_imp_VarP:
"{ SubstTermP v i t u } ⊢ VarP v"   (is ?thvar)
proof -
obtain s::name and k::name  where "atom s ♯ (v,i,t,u,k)" "atom k ♯ (v,i,t,u)"
by (metis obtain_fresh)
thus ?thesis1 ?thsf ?thterm ?thvar
by (auto intro: SeqStTermP_imp_VarP thin2)
qed

lemma SubstTermP_subst [simp]:
"(SubstTermP v i t u)(j::=w) = SubstTermP (subst j w v) (subst j w i) (subst j w t) (subst j w u)"
proof -
obtain s::name and k::name
where "atom s ♯ (v,i,t,u,w,j,k)"  "atom k ♯ (v,i,t,u,w,j)"
by (metis obtain_fresh)
thus ?thesis
by (simp add: SubstTermP.simps [of s _ _ _ _ k])
qed

lemma SubstTermP_cong:
"⟦H ⊢ v EQ v'; H ⊢ i EQ i'; H ⊢ t EQ t'; H ⊢ u EQ u'⟧
⟹ H ⊢ SubstTermP v i t u IFF SubstTermP v' i' t' u'"
by (rule P4_cong) auto

declare SubstTermP.simps [simp del]

section ‹Abstraction over formulas›

subsection ‹The predicate ‹AbstAtomicP››

nominal_function AbstAtomicP :: "tm ⇒ tm ⇒ tm ⇒ tm ⇒ fm"
where "⟦atom t ♯ (v,i,y,y',t',u,u'); atom t' ♯ (v,i,y,y',u,u');
atom u ♯ (v,i,y,y',u'); atom u' ♯ (v,i,y,y')⟧ ⟹
AbstAtomicP v i y y' =
Ex t (Ex u (Ex t' (Ex u'
(AbstTermP v i (Var t) (Var t') AND AbstTermP v i (Var u) (Var u') AND
((y EQ Q_Eq (Var t) (Var u) AND y' EQ Q_Eq (Var t') (Var u')) OR
(y EQ Q_Mem (Var t) (Var u) AND y' EQ Q_Mem (Var t') (Var u')))))))"
by (auto simp: eqvt_def AbstAtomicP_graph_aux_def flip_fresh_fresh) (metis obtain_fresh)

nominal_termination (eqvt)
by lexicographic_order

lemma
shows AbstAtomicP_fresh_iff [simp]:
"a ♯ AbstAtomicP v i y y' ⟷ a ♯ v ∧ a ♯ i ∧ a ♯ y ∧ a ♯ y'"         (is ?thesis1)
and AbstAtomicP_sf [iff]: "Sigma_fm (AbstAtomicP v i y y')"              (is ?thsf)
proof -
obtain t::name and u::name and t'::name  and u'::name
where "atom t ♯ (v,i,y,y',t',u,u')" "atom t' ♯ (v,i,y,y',u,u')"
"atom u ♯ (v,i,y,y',u')" "atom u' ♯ (v,i,y,y')"
by (metis obtain_fresh)
thus ?thesis1 ?thsf
by auto
qed

lemma AbstAtomicP_subst [simp]:
"(AbstAtomicP v tm y y')(i::=w) = AbstAtomicP (subst i w v) (subst i w tm) (subst i w y) (subst i w y')"
proof -
obtain t::name and u::name and t'::name  and u'::name
where "atom t ♯ (v,tm,y,y',w,i,t',u,u')"  "atom t' ♯ (v,tm,y,y',w,i,u,u')"
"atom u ♯ (v,tm,y,y',w,i,u')"       "atom u' ♯ (v,tm,y,y',w,i)"
by (metis obtain_fresh)
thus ?thesis
by (simp add: AbstAtomicP.simps [of t _ _ _ _ t' u u'])
qed

declare AbstAtomicP.simps [simp del]

subsection ‹The predicate ‹AbsMakeForm››

nominal_function SeqAbstFormP :: "tm ⇒ tm ⇒ tm ⇒ tm ⇒ tm ⇒ tm ⇒ fm"
where "⟦atom l ♯ (s,k,v,sli,sl,sl',m,n,smi,sm,sm',sni,sn,sn');
atom sli ♯ (s,v,sl,sl',m,n,smi,sm,sm',sni,sn,sn');
atom sl ♯ (s,v,sl',m,n,smi,sm,sm',sni,sn,sn');
atom sl' ♯ (s,v,m,n,smi,sm,sm',sni,sn,sn');
atom m ♯ (s,n,smi,sm,sm',sni,sn,sn');
atom n ♯ (s,smi,sm,sm',sni,sn,sn'); atom smi ♯ (s,sm,sm',sni,sn,sn');
atom sm ♯ (s,sm',sni,sn,sn'); atom sm' ♯ (s,sni,sn,sn');
atom sni ♯ (s,sn,sn'); atom sn ♯ (s,sn'); atom sn' ♯ (s)⟧ ⟹
SeqAbstFormP v i x x' s k =
LstSeqP s k (HPair i (HPair x x')) AND
All2 l (SUCC k) (Ex sli (Ex sl (Ex sl' (HPair (Var l) (HPair (Var sli) (HPair (Var sl) (Var sl'))) IN s AND
(AbstAtomicP v (Var sli) (Var sl) (Var sl') OR
OrdP (Var sli) AND
Ex m (Ex n (Ex smi (Ex sm (Ex sm' (Ex sni (Ex sn (Ex sn'
(Var m IN Var l AND Var n IN Var l AND
HPair (Var m) (HPair (Var smi) (HPair (Var sm) (Var sm'))) IN s AND
HPair (Var n) (HPair (Var sni) (HPair (Var sn) (Var sn'))) IN s AND
((Var sli EQ Var smi AND Var sli EQ Var sni AND
Var sl EQ Q_Disj (Var sm) (Var sn) AND
Var sl' EQ Q_Disj (Var sm') (Var sn')) OR
(Var sli EQ Var smi AND
Var sl EQ Q_Neg (Var sm) AND Var sl' EQ Q_Neg (Var sm')) OR
(SUCC (Var sli) EQ Var smi AND
Var sl EQ Q_Ex (Var sm) AND Var sl' EQ Q_Ex (Var sm'))))))))))))))))"
by (auto simp: eqvt_def SeqAbstFormP_graph_aux_def flip_fresh_fresh) (metis obtain_fresh)

nominal_termination (eqvt)
by lexicographic_order

lemma
shows SeqAbstFormP_fresh_iff [simp]:
"a ♯ SeqAbstFormP v i x x' s k ⟷ a ♯ v ∧ a ♯ i ∧ a ♯ x ∧ a ♯ x' ∧ a ♯ s ∧ a ♯ k"  (is ?thesis1)
and SeqAbstFormP_sf [iff]:
"Sigma_fm (SeqAbstFormP v i x x' s k)"  (is ?thsf)
and SeqAbstFormP_imp_OrdP:
"{ SeqAbstFormP v u x x' s k } ⊢ OrdP k"  (is ?thOrd)
and SeqAbstFormP_imp_LstSeqP:
"{ SeqAbstFormP v u x x' s k } ⊢ LstSeqP s k (HPair u (HPair x x'))"  (is ?thLstSeq)
proof -
obtain l::name and sli::name and sl::name and sl'::name and m::name and n::name and
smi::name and sm::name and sm'::name and sni::name and sn::name and sn'::name
where atoms:
"atom l ♯ (s,k,v,sli,sl,sl',m,n,smi,sm,sm',sni,sn,sn')"
"atom sli ♯ (s,v,sl,sl',m,n,smi,sm,sm',sni,sn,sn')"
"atom sl ♯ (s,v,sl',m,n,smi,sm,sm',sni,sn,sn')"
"atom sl' ♯ (s,v,m,n,smi,sm,sm',sni,sn,sn')"
"atom m ♯ (s,n,smi,sm,sm',sni,sn,sn')" "atom n ♯ (s,smi,sm,sm',sni,sn,sn')"
"atom smi ♯ (s,sm,sm',sni,sn,sn')"
"atom sm ♯ (s,sm',sni,sn,sn')"
"atom sm' ♯ (s,sni,sn,sn')"
"atom sni ♯ (s,sn,sn')" "atom sn ♯ (s,sn')" "atom sn' ♯ s"
by (metis obtain_fresh)
thus ?thesis1 ?thsf ?thOrd ?thLstSeq
by (auto intro: LstSeqP_OrdP)
qed

lemma SeqAbstFormP_subst [simp]:
"(SeqAbstFormP v u x x' s k)(i::=t) =
SeqAbstFormP (subst i t v) (subst i t u) (subst i t x) (subst i t x') (subst i t s) (subst i t k)"
proof -
obtain l::name and sli::name and sl::name and sl'::name and m::name and n::name and
smi::name and sm::name and sm'::name and sni::name and sn::name and sn'::name
where "atom l ♯ (i,t,s,k,v,sli,sl,sl',m,n,smi,sm,sm',sni,sn,sn')"
"atom sli ♯ (i,t,s,v,sl,sl',m,n,smi,sm,sm',sni,sn,sn')"
"atom sl ♯ (i,t,s,v,sl',m,n,smi,sm,sm',sni,sn,sn')"
"atom sl' ♯ (i,t,s,v,m,n,smi,sm,sm',sni,sn,sn')"
"atom m ♯ (i,t,s,n,smi,sm,sm',sni,sn,sn')"
"atom n ♯ (i,t,s,smi,sm,sm',sni,sn,sn')"
"atom smi ♯ (i,t,s,sm,sm',sni,sn,sn')"
"atom sm ♯ (i,t,s,sm',sni,sn,sn')" "atom sm' ♯ (i,t,s,sni,sn,sn')"
"atom sni ♯ (i,t,s,sn,sn')" "atom sn ♯ (i,t,s,sn')" "atom sn' ♯ (i,t,s)"
by (metis obtain_fresh)
thus ?thesis
by (force simp add: SeqAbstFormP.simps [of l _ _ _ sli sl sl' m n smi sm sm' sni sn sn'])
qed

declare SeqAbstFormP.simps [simp del]

subsection ‹Defining the syntax: the main AbstForm predicate›

nominal_function AbstFormP :: "tm ⇒ tm ⇒ tm ⇒ tm ⇒ fm"
where "⟦atom s ♯ (v,i,x,x',k);
atom k ♯ (v,i,x,x')⟧ ⟹
AbstFormP v i x x' = VarP v AND OrdP i AND Ex s (Ex k (SeqAbstFormP v i x x' (Var s) (Var k)))"
by (auto simp: eqvt_def AbstFormP_graph_aux_def flip_fresh_fresh) (metis obtain_fresh)

nominal_termination (eqvt)
by lexicographic_order

lemma
shows AbstFormP_fresh_iff [simp]:
"a ♯ AbstFormP v i x x' ⟷ a ♯ v ∧ a ♯ i ∧ a ♯ x ∧ a ♯ x'" (is ?thesis1)
and AbstFormP_sf [iff]:
"Sigma_fm (AbstFormP v i x x')"    (is ?thsf)
proof -
obtain s::name and k::name  where "atom s ♯ (v,i,x,x',k)" "atom k ♯ (v,i,x,x')"
by (metis obtain_fresh)
thus ?thesis1 ?thsf
by auto
qed

lemma AbstFormP_subst [simp]:
"(AbstFormP v i x x')(j::=t) = AbstFormP (subst j t v) (subst j t i) (subst j t x) (subst j t x')"
proof -
obtain s::name and k::name  where "atom s ♯ (v,i,x,x',t,j,k)" "atom k ♯ (v,i,x,x',t,j)"
by (metis obtain_fresh)
thus ?thesis
by (auto simp: AbstFormP.simps [of s _ _ _ _ k])
qed

declare AbstFormP.simps [simp del]

section ‹Substitution over formulas›

subsection ‹The predicate ‹SubstAtomicP››

nominal_function SubstAtomicP :: "tm ⇒ tm ⇒ tm ⇒ tm ⇒ fm"
where "⟦atom t ♯ (v,tm,y,y',t',u,u');
atom t' ♯ (v,tm,y,y',u,u');
atom u ♯ (v,tm,y,y',u');
atom u' ♯ (v,tm,y,y')⟧ ⟹
SubstAtomicP v tm y y' =
Ex t (Ex u (Ex t' (Ex u'
(SubstTermP v tm (Var t) (Var t') AND SubstTermP v tm (Var u) (Var u') AND
((y EQ Q_Eq (Var t) (Var u) AND y' EQ Q_Eq (Var t') (Var u')) OR
(y EQ Q_Mem (Var t) (Var u) AND y' EQ Q_Mem (Var t') (Var u')))))))"
by (auto simp: eqvt_def SubstAtomicP_graph_aux_def flip_fresh_fresh) (metis obtain_fresh)

nominal_termination (eqvt)
by lexicographic_order

lemma
shows SubstAtomicP_fresh_iff [simp]:
"a ♯ SubstAtomicP v tm y y' ⟷ a ♯ v ∧ a ♯ tm ∧ a ♯ y ∧ a ♯ y'"           (is ?thesis1)
and SubstAtomicP_sf [iff]: "Sigma_fm (SubstAtomicP v tm y y')"               (is ?thsf)
proof -
obtain t::name and u::name and t'::name  and u'::name
where "atom t ♯ (v,tm,y,y',t',u,u')" "atom t' ♯ (v,tm,y,y',u,u')"
"atom u ♯ (v,tm,y,y',u')" "atom u' ♯ (v,tm,y,y')"
by (metis obtain_fresh)
thus ?thesis1 ?thsf
by auto
qed

lemma SubstAtomicP_subst [simp]:
"(SubstAtomicP v tm y y')(i::=w) = SubstAtomicP (subst i w v) (subst i w tm) (subst i w y) (subst i w y')"
proof -
obtain t::name and u::name and t'::name  and u'::name
where "atom t ♯ (v,tm,y,y',w,i,t',u,u')" "atom t' ♯ (v,tm,y,y',w,i,u,u')"
"atom u ♯ (v,tm,y,y',w,i,u')" "atom u' ♯ (v,tm,y,y',w,i)"
by (metis obtain_fresh)
thus ?thesis
by (simp add: SubstAtomicP.simps [of t _ _ _ _ t' u u'])
qed

lemma SubstAtomicP_cong:
"⟦H ⊢ v EQ v'; H ⊢ tm EQ tm'; H ⊢ x EQ x'; H ⊢ y EQ y'⟧
⟹ H ⊢ SubstAtomicP v tm x y IFF SubstAtomicP v' tm' x' y'"
by (rule P4_cong) auto

subsection ‹The predicate ‹SubstMakeForm››

nominal_function SeqSubstFormP :: "tm ⇒ tm ⇒ tm ⇒ tm ⇒ tm ⇒ tm ⇒ fm"
where "⟦atom l ♯ (s,k,v,u,sl,sl',m,n,sm,sm',sn,sn');
atom sl ♯ (s,v,u,sl',m,n,sm,sm',sn,sn');
atom sl' ♯ (s,v,u,m,n,sm,sm',sn,sn');
atom m ♯ (s,n,sm,sm',sn,sn'); atom n ♯ (s,sm,sm',sn,sn');
atom sm ♯ (s,sm',sn,sn'); atom sm' ♯ (s,sn,sn');
atom sn ♯ (s,sn'); atom sn' ♯ s⟧ ⟹
SeqSubstFormP v u x x' s k =
LstSeqP s k (HPair x x') AND
All2 l (SUCC k) (Ex sl (Ex sl' (HPair (Var l) (HPair (Var sl) (Var sl')) IN s AND
(SubstAtomicP v u (Var sl) (Var sl') OR
Ex m (Ex n (Ex sm (Ex sm' (Ex sn (Ex sn' (Var m IN Var l AND Var n IN Var l AND
HPair (Var m) (HPair (Var sm) (Var sm')) IN s AND
HPair (Var n) (HPair (Var sn) (Var sn')) IN s AND
((Var sl EQ Q_Disj (Var sm) (Var sn) AND
Var sl' EQ Q_Disj (Var sm') (Var sn')) OR
(Var sl EQ Q_Neg (Var sm) AND Var sl' EQ Q_Neg (Var sm')) OR
(Var sl EQ Q_Ex (Var sm) AND Var sl' EQ Q_Ex (Var sm')))))))))))))"
apply (simp_all add: eqvt_def SeqSubstFormP_graph_aux_def flip_fresh_fresh)
by auto (metis obtain_fresh)

nominal_termination (eqvt)
by lexicographic_order

lemma
shows SeqSubstFormP_fresh_iff [simp]:
"a ♯ SeqSubstFormP v u x x' s k ⟷ a ♯ v ∧ a ♯ u ∧ a ♯ x ∧ a ♯ x' ∧ a ♯ s ∧ a ♯ k"  (is ?thesis1)
and SeqSubstFormP_sf [iff]:
"Sigma_fm (SeqSubstFormP v u x x' s k)"  (is ?thsf)
and SeqSubstFormP_imp_OrdP:
"{ SeqSubstFormP v u x x' s k } ⊢ OrdP k"  (is ?thOrd)
and SeqSubstFormP_imp_LstSeqP:
"{ SeqSubstFormP v u x x' s k } ⊢ LstSeqP s k (HPair x x')"  (is ?thLstSeq)
proof -
obtain l::name and sl::name and sl'::name and m::name and n::name and
sm::name and sm'::name and sn::name and sn'::name
where atoms:
"atom l ♯ (s,k,v,u,sl,sl',m,n,sm,sm',sn,sn')"
"atom sl ♯ (s,v,u,sl',m,n,sm,sm',sn,sn')"
"atom sl' ♯ (s,v,u,m,n,sm,sm',sn,sn')"
"atom m ♯ (s,n,sm,sm',sn,sn')" "atom n ♯ (s,sm,sm',sn,sn')"
"atom sm ♯ (s,sm',sn,sn')" "atom sm' ♯ (s,sn,sn')"
"atom sn ♯ (s,sn')" "atom sn' ♯ (s)"
by (metis obtain_fresh)
thus ?thesis1 ?thsf ?thOrd ?thLstSeq
by (auto intro: LstSeqP_OrdP)
qed

lemma SeqSubstFormP_subst [simp]:
"(SeqSubstFormP v u x x' s k)(i::=t) =
SeqSubstFormP (subst i t v) (subst i t u) (subst i t x) (subst i t x') (subst i t s) (subst i t k)"
proof -
obtain l::name and sl::name and sl'::name and m::name and n::name and
sm::name and sm'::name and sn::name and sn'::name
where "atom l ♯ (s,k,v,u,t,i,sl,sl',m,n,sm,sm',sn,sn')"
"atom sl ♯ (s,v,u,t,i,sl',m,n,sm,sm',sn,sn')"
"atom sl' ♯ (s,v,u,t,i,m,n,sm,sm',sn,sn')"
"atom m ♯ (s,t,i,n,sm,sm',sn,sn')" "atom n ♯ (s,t,i,sm,sm',sn,sn')"
"atom sm ♯ (s,t,i,sm',sn,sn')" "atom sm' ♯ (s,t,i,sn,sn')"
"atom sn ♯ (s,t,i,sn')" "atom sn' ♯ (s,t,i)"
by (metis obtain_fresh)
thus ?thesis
by (force simp add: SeqSubstFormP.simps [of l _ _ _ _ sl sl' m n sm sm' sn sn'])
qed

lemma SeqSubstFormP_cong:
"⟦H ⊢ t EQ t'; H ⊢ u EQ u'; H ⊢ s EQ s'; H ⊢ k EQ k'⟧
⟹ H ⊢ SeqSubstFormP v i t u s k IFF SeqSubstFormP v i t' u' s' k'"
by (rule P4_cong [where tms="[v,i]"]) (auto simp: fresh_Cons)

declare SeqSubstFormP.simps [simp del]

subsection ‹Defining the syntax: the main SubstForm predicate›

nominal_function SubstFormP :: "tm ⇒ tm ⇒ tm ⇒ tm ⇒ fm"
where "⟦atom s ♯ (v,i,x,x',k); atom k ♯ (v,i,x,x')⟧ ⟹
SubstFormP v i x x' =
VarP v AND TermP i AND Ex s (Ex k (SeqSubstFormP v i x x' (Var s) (Var k)))"
by (auto simp: eqvt_def SubstFormP_graph_aux_def flip_fresh_fresh) (metis obtain_fresh)

nominal_termination (eqvt)
by lexicographic_order

lemma
shows SubstFormP_fresh_iff [simp]:
"a ♯ SubstFormP v i x x' ⟷ a ♯ v ∧ a ♯ i ∧ a ♯ x ∧ a ♯ x'"  (is ?thesis1)
and SubstFormP_sf [iff]:
"Sigma_fm (SubstFormP v i x x')"  (is ?thsf)
proof -
obtain s::name and k::name
where "atom s ♯ (v,i,x,x',k)"  "atom k ♯ (v,i,x,x')"
by (metis obtain_fresh)
thus ?thesis1 ?thsf
by auto
qed

lemma SubstFormP_subst [simp]:
"(SubstFormP v i x x')(j::=t) = SubstFormP (subst j t v) (subst j t i) (subst j t x) (subst j t x')"
proof -
obtain s::name and k::name  where "atom s ♯ (v,i,x,x',t,j,k)" "atom k ♯ (v,i,x,x',t,j)"
by (metis obtain_fresh)
thus ?thesis
by (auto simp: SubstFormP.simps [of s _ _ _ _ k])
qed

lemma SubstFormP_cong:
"⟦H ⊢ v EQ v'; H ⊢ i EQ i'; H ⊢ t EQ t'; H ⊢ u EQ u'⟧
⟹ H ⊢ SubstFormP v i t u IFF SubstFormP v' i' t' u'"
by (rule P4_cong) auto

lemma ground_SubstFormP [simp]: "ground_fm (SubstFormP v y x x') ⟷ ground v ∧ ground y ∧ ground x ∧ ground x'"
by (auto simp: ground_aux_def ground_fm_aux_def supp_conv_fresh)

declare SubstFormP.simps [simp del]

section ‹The predicate ‹AtomicP››

nominal_function AtomicP :: "tm ⇒ fm"
where "⟦atom t ♯ (u,y); atom u ♯ y⟧ ⟹
AtomicP y = Ex t (Ex u (TermP (Var t) AND TermP (Var u) AND
(y EQ Q_Eq (Var t) (Var u) OR
y EQ Q_Mem (Var t) (Var u))))"
by (auto simp: eqvt_def AtomicP_graph_aux_def flip_fresh_fresh) (metis obtain_fresh)

nominal_termination (eqvt)
by lexicographic_order

lemma
shows AtomicP_fresh_iff [simp]: "a ♯ AtomicP y ⟷ a ♯ y"    (is ?thesis1)
and AtomicP_sf [iff]: "Sigma_fm (AtomicP y)"  (is ?thsf)
proof -
obtain t::name and u::name  where "atom t ♯ (u,y)"  "atom u ♯ y"
by (metis obtain_fresh)
thus ?thesis1 ?thsf
by auto
qed

lemma AtompicP_subst [simp]: "(AtomicP t)(j::=w) = AtomicP (subst j w t)"
proof -
obtain x y :: name where "atom x ♯ (j,w,t,y)"   "atom y ♯ (j,w,t)"
by (metis obtain_fresh)
thus ?thesis
by (auto simp: AtomicP.simps [of x y])
qed

section ‹The predicate ‹MakeForm››

nominal_function MakeFormP :: "tm ⇒ tm ⇒ tm ⇒ fm"
where "⟦atom v ♯ (y,u,w,au); atom au ♯ (y,u,w)⟧ ⟹
MakeFormP y u w =
y EQ Q_Disj u w OR y EQ Q_Neg u OR
Ex v (Ex au (AbstFormP (Var v) Zero u (Var au) AND y EQ Q_Ex (Var au)))"
by (auto simp: eqvt_def MakeFormP_graph_aux_def flip_fresh_fresh) (metis obtain_fresh)

nominal_termination (eqvt)
by lexicographic_order

lemma
shows MakeFormP_fresh_iff [simp]:
"a ♯ MakeFormP y u w ⟷ a ♯ y ∧ a ♯ u ∧ a ♯ w"  (is ?thesis1)
and MakeFormP_sf [iff]:
"Sigma_fm (MakeFormP y u w)"  (is ?thsf)
proof -
obtain v::name and au::name  where "atom v ♯ (y,u,w,au)"  "atom au ♯ (y,u,w)"
by (metis obtain_fresh)
thus ?thesis1 ?thsf
by auto
qed

declare MakeFormP.simps [simp del]

lemma MakeFormP_subst [simp]: "(MakeFormP y u t)(j::=w) = MakeFormP (subst j w y) (subst j w u) (subst j w t)"
proof -
obtain a b :: name where "atom a ♯ (j,w,y,u,t,b)"   "atom b ♯ (j,w,y,u,t)"
by (metis obtain_fresh)
thus ?thesis
by (auto simp: MakeFormP.simps [of a _ _ _ b])
qed

section ‹The predicate ‹SeqFormP››

(*SeqForm(s,k,t) ≡ LstSeq(s,k,t) ∧ (∀n∈k)[Atomic (s n) ∨ (∃m,l∈n)[MakeForm (s m) (s l) (s n)]]*)

nominal_function SeqFormP :: "tm ⇒ tm ⇒ tm ⇒ fm"
where "⟦atom l ♯ (s,k,t,sl,m,n,sm,sn); atom sl ♯ (s,k,t,m,n,sm,sn);
atom m ♯ (s,k,t,n,sm,sn); atom n ♯ (s,k,t,sm,sn);
atom sm ♯ (s,k,t,sn); atom sn ♯ (s,k,t)⟧ ⟹
SeqFormP s k t =
LstSeqP s k t AND
All2 n (SUCC k) (Ex sn (HPair (Var n) (Var sn) IN s AND (AtomicP (Var sn) OR
Ex m (Ex l (Ex sm (Ex sl (Var m IN Var n AND Var l IN Var n AND
HPair (Var m) (Var sm) IN s AND HPair (Var l) (Var sl) IN s AND
MakeFormP (Var sn) (Var sm) (Var sl))))))))"
by (auto simp: eqvt_def SeqFormP_graph_aux_def flip_fresh_fresh) (metis obtain_fresh)

nominal_termination (eqvt)
by lexicographic_order

lemma
shows SeqFormP_fresh_iff [simp]:
"a ♯ SeqFormP s k t ⟷ a ♯ s ∧ a ♯ k ∧ a ♯ t" (is ?thesis1)
and SeqFormP_sf [iff]: "Sigma_fm (SeqFormP s k t)"          (is ?thsf)
and SeqFormP_imp_OrdP:
"{ SeqFormP s k t } ⊢ OrdP k"  (is ?thOrd)
and SeqFormP_imp_LstSeqP:
"{ SeqFormP s k t } ⊢ LstSeqP s k t"  (is ?thLstSeq)
proof -
obtain l::name and sl::name and m::name and n::name and sm::name and sn::name
where atoms: "atom l ♯ (s,k,t,sl,m,n,sm,sn)"   "atom sl ♯ (s,k,t,m,n,sm,sn)"
"atom m ♯ (s,k,t,n,sm,sn)"   "atom n ♯ (s,k,t,sm,sn)"
"atom sm ♯ (s,k,t,sn)"       "atom sn ♯ (s,k,t)"
by (metis obtain_fresh)
thus ?thesis1 ?thsf ?thOrd ?thLstSeq
by (auto intro: LstSeqP_OrdP)
qed

lemma SeqFormP_subst [simp]:
"(SeqFormP s k t)(j::=w) = SeqFormP (subst j w s) (subst j w k) (subst j w t)"
proof -
obtain l::name and sl::name and m::name and n::name and sm::name and sn::name
where "atom l ♯ (j,w,s,t,k,sl,m,n,sm,sn)"   "atom sl ♯ (j,w,s,k,t,m,n,sm,sn)"
"atom m ♯ (j,w,s,k,t,n,sm,sn)"   "atom n ♯ (j,w,s,k,t,sm,sn)"
"atom sm ♯ (j,w,s,k,t,sn)"   "atom sn ♯ (j,w,s,k,t)"
by (metis obtain_fresh)
thus ?thesis
by (auto simp: SeqFormP.simps [of l _ _ _ sl m n sm sn])
qed

section ‹The predicate ‹FormP››

subsection ‹Definition›

nominal_function FormP :: "tm ⇒ fm"
where "⟦atom k ♯ (s,y); atom s ♯ y⟧ ⟹
FormP y = Ex k (Ex s (SeqFormP (Var s) (Var k) y))"
by (auto simp: eqvt_def FormP_graph_aux_def flip_fresh_fresh) (metis obtain_fresh)

nominal_termination (eqvt)
by lexicographic_order

lemma
shows FormP_fresh_iff [simp]: "a ♯ FormP y ⟷ a ♯ y"              (is ?thesis1)
and FormP_sf [iff]:         "Sigma_fm (FormP y)"                 (is ?thsf)
proof -
obtain k::name and s::name  where k: "atom k ♯ (s,y)" "atom s ♯ y"
by (metis obtain_fresh)
thus ?thesis1 ?thsf
by auto
qed

lemma FormP_subst [simp]: "(FormP y)(j::=w) = FormP (subst j w y)"
proof -
obtain k::name and s::name where "atom k ♯ (s,j,w,y)"  "atom s ♯ (j,w,y)"
by (metis obtain_fresh)
thus ?thesis
by (auto simp: FormP.simps [of k s])
qed

subsection ‹The predicate ‹VarNonOccFormP› (Derived from ‹SubstFormP›)›

nominal_function VarNonOccFormP :: "tm ⇒ tm ⇒ fm"
where "VarNonOccFormP v x = FormP x AND SubstFormP v Zero x x"
by (auto simp: eqvt_def VarNonOccFormP_graph_aux_def)

nominal_termination (eqvt)
by lexicographic_order

lemma
shows VarNonOccFormP_fresh_iff [simp]: "a ♯ VarNonOccFormP v y ⟷ a ♯ v ∧ a ♯ y" (is ?thesis1)
and VarNonOccFormP_sf [iff]: "Sigma_fm (VarNonOccFormP v y)" (is ?thsf)
proof -
show ?thesis1 ?thsf
by auto
qed

declare VarNonOccFormP.simps [simp del]

end

```